A Cross-Case Study: Comparing the Role of Science Centers in Advancing Scientific Knowledge in Turkey and Denmark - İdin, Şahin (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2021)
This study aimed to investigate the role of science centers in advancing scientific knowledge. To do so, two heads of science centers were selected to perform interviews, one of whom had previously worked as a head of science center in Denmark and the other of whom had previously worked as a head of science center in Turkey. The study's approach was modified as qualitative method, and the study can be thought of as a case study in this context. As a data collection tool, a semi-structured interview form was used. It was used to find out what the participants thought about the role of science centers in advancing scientific knowledge. Participants emphasize the importance of science centers in achieving effective science communication. This research is expected to guide future studies on the advancement of the scientific knowledge.